Performance analysis of a self‐protection system for vehicles in case of WUI fire entrapment. (25th April 2020) - Pastor, Elsa; Àgueda, Alba; Sebastià, Juan; Mata, Christian; Valero, Mario M.; Planas, Eulàlia
Summary: We present the experimental performance analysis of a fire protection fabric for cars designed to protect people's life in case of fire entrapment. Two experimental burns were executed to simulate heat and smoke exposure conditions in case of vehicle entrapment in a rural road. For the first experimental burn, a 2‐m high fuel bed of pine slash was arranged in a 13 m × 6 m area. Fire was ignited at one end of the fuel bed and spread wind driven (3 m/s midflame wind speed). 2.8 m away from the other fuel bed end, a car covered with the fabric was placed parallel to the fire. Data analysis provided values of fire behavior and flame characteristics, being typical of wildfires of moderate intensity (1800 kW/m). Maximum air temperatures inside the vehicle ranged around 41°C to 42.5°C, providing evidence of the fabric's good performance. To evaluate the degree of protection against smoke, air change rates were estimated with and without the fabric covering the car. Also, an experimental burn similar to the previous one was executed to monitor CO2 and CO concentrations inside the car. Tenable conditions for these gases were maintained during the whole test according to reviewed exposure criteria.